A novel Generalized State-Space Averaging (GSSA) model for advanced aircraft electric power systems. (1st January 2015) - Ebrahimi, Hadi; El-Kishky, Hassan
Highlights: A study model is developed for aircraft electric power systems. A novel GSSA model is developed for the interconnected power grid. The system's dynamics are characterized under various conditions. The averaged results are compared and verified with the actual model. The obtained measured values are validated with available aircraft standards. Abstract: The growing complexity of Advanced Aircraft Electric Power Systems (AAEPS) has made conventional state-space averaging models inadequate for systems analysis and characterization. This paper presents a novel Generalized State-Space Averaging (GSSA) model for the system analysis, control and characterization of AAEPS. The primary objective of this paper is to introduce a mathematically elegant and computationally simple model to copy the AAEPS behavior at the critical nodes of the electric grid. Also, to reduce some or all of the drawbacks (complexity, cost, simulation time…, etc) associated with sensor-based monitoring and computer aided design software simulations popularly used for AAEPS characterization. It is shown in this paper that the GSSA approach overcomes the limitations of the conventional state-space averaging method, which fails to predict the behavior of AC signals in a circuit analysis. Unlike conventional averaging method, the GSSA model presented in this paper includes both DC and AC components. This would capture the key dynamic and steady-state characteristics of the aircraft electric systems. The developed model is then examined for the aircraft system's visualization and accuracy of computation under different loading scenarios. Through several case studies, the applicability and effectiveness of the GSSA method is verified by comparing to the actual real-time simulation model obtained from Powersim 9 (PSIM9) software environment. The simulations results represent voltage, current and load power at the major nodes of the AAEPS. It has been demonstrated that the obtained results from GSSA model in Matlab® closely agree with those of obtained in an actual AAEPS implemented in PSIM9 software.